Genetics of Keratoconus: Where Do We Stand? - Khaled K. Abu-Amero; Abdulrahman M. Al-Muammar; Altaf A. Kondkar (Journal of Ophthalmology)
Keratoconus is a progressive thinning and anterior protrusion of the cornea that results in steepening and distortion of the cornea, altered refractive powers, and reduced vision. Keratoconus has a complex multifactorial etiology, with environmental, behavioral, and multiple genetic components contributing to the disease pathophysiology. Using genome-wide and candidate gene approaches several genomic loci and genes have been identified that highlight the complex molecular etiology of this disease. The review focuses on current knowledge of these genetic risk factors associated with keratoconus.